Membrane Topology and Heme Binding of the Histidine Kinases HrrS and ChrS in Corynebacterium glutamicum - Keppel, Marc; Davoudi, Eva; Gätgens, Cornelia; Frunzke, Julia (Frontiers in Microbiology, 2018)
The HrrSA and the ChrSA two-component systems play a central role in the coordination of heme homeostasis in the Gram-positive soil bacterium Corynebacterium glutamicum and the prominent pathogen Corynebacterium diphtheriae, both members of the Corynebacteriaceae. In this study, we have performed a comparative analysis of the membrane topology and heme-binding characteristics of the histidine kinases HrrS and ChrS of C. glutamicum. While the cytoplasmic catalytic domains are highly conserved between HrrS and ChrS, the N-terminal sensing parts share only minor sequence similarity. PhoA and LacZ fusions of the N-terminal sensor domains of HrrS and ChrS revealed that both proteins are embedded into the cytoplasmic membrane via six α-helices. Although the overall membrane topology appeared to be conserved, target gene profiling indicated a higher sensitivity of the ChrS system to low heme levels (<1 M). In vitro, solubilized and purified full-length proteins bound heme in a 1:1 stoichiometry per monomer. Further on, alanine-scanning of conserved amino acid residues in the N-terminal sensor domain revealed three aromatic residues (Y112, F115, and F118), which apparently contribute to heme-binding of HrrS. Exchange of either one or all three residues resulted in an almost abolished heme-binding of HrrS in vitro. In contrast, ChrS mutants only displayed a red shift of the soret band from 406 to 418 nm suggesting an altered set of ligands in the triple mutant. In line with target gene profiling, these in vitro studies suggest distinct differences in the heme-protein interface of HrrS and ChrS. Since the membrane topology mapping displayed no extensive loop regions and alanine-scanning revealed potential heme-binding residues in alpha helix number four, we propose an intramembrane sensing mechanism for both proteins. Overall, we present a first comparative analysis of the ChrS and HrrS kinases functioning as transient heme sensors in the Corynebacteriaceae.